(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This article explores the features of developing communicative competence in students within a multilingual environment. Communicative competence encompasses the ability to effectively and appropriately use language for communication in various contexts. In a multilingual environment, students are exposed to multiple languages, cultures, and communication styles, which presents unique opportunities and challenges for their language development. The article highlights key features, including language role models, language tasks and projects, error correction and feedback, language maintenance and revitalization, and multimodal communication. It also discusses the importance of language awareness, language learning strategies, language mediation, and community engagement. Additionally, the article emphasizes the significance of language policy, assessment practices, and ongoing professional development for educators. These features collectively contribute to the holistic development of communicative competence in students within a multilingual environment.